The Return of the Womb or the Gaia of Meaning: Mother Tongue - Tek, Ayhan ([EN], 2018)
The mother tongue has a very strong relationship with mind, psychology and "mother archetype". It is assumed that the individuals who have a strong relationship with their mother tongue in their personal and social lives have a strong psychological disposition. Especially in the context of Jung's mother archetype theory, it is observed that people who face fear and similar traumatic situations take shelter in the archetype. In this study, we will focus on six different cases related to mother tongue in the context of Jung's theory. As will be manifested in the six cases, the mother tongue has great impact on human psychology. The results point to mythological archetypes. It is observed that there is a desire to return to the mother's womb as a symptom in people who have detached from their mother tongue. Concordantly, this study focuses on the trauma behind it and the returning process of those individuals who have severed their ties with their mother tongue.Key Words:mother tongue, mother archetype, Jung, womb.